2020
DOI: 10.1186/s12872-020-01529-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of rolipram on endotoxic cardiac dysfunction via inhibition of the inflammatory response in cardiac fibroblasts

Abstract: Background Cardiac fibroblasts, regarded as the immunomodulatory hub of the heart, have been thought to play an important role during sepsis-induced cardiomyopathy (SIC). However, the detailed molecular mechanism and targeted therapies for SIC are still lacking. Therefore, we sought to investigate the likely protective effects of rolipram, an anti-inflammatory drug, on lipopolysaccharide (LPS)-stimulated inflammatory responses in cardiac fibroblasts and on cardiac dysfunction in endotoxic mice. Method Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…AngII-induced cardiac remodeling is characterized by a pathophysiological response to chronic inflammation with progressive fibrosis (Zhao et al, 2019;Lin et al, 2021). In this process, an inflammatory milieu can promote the phenotypic transformation of cardiac fibroblasts (Ji et al, 2020). AngII is known to have a strong proinflammatory and reported profibrotic effects on facilitating the synthesis of ECM and further contributing to myocardial fibrosis with increased expression of cytokines such as IL-1β, IL-6, and TNF-α (She et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…AngII-induced cardiac remodeling is characterized by a pathophysiological response to chronic inflammation with progressive fibrosis (Zhao et al, 2019;Lin et al, 2021). In this process, an inflammatory milieu can promote the phenotypic transformation of cardiac fibroblasts (Ji et al, 2020). AngII is known to have a strong proinflammatory and reported profibrotic effects on facilitating the synthesis of ECM and further contributing to myocardial fibrosis with increased expression of cytokines such as IL-1β, IL-6, and TNF-α (She et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They promote a response to insult in association with the immune system. Bacteria can trigger fibroblasts to produce inflammatory mediators (cytokines, chemokines, and growth factors) that recruit inflammatory cells from the circulation, amplifying the inflammatory process and inducing heart dysfunction through atherogenesis [ 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It increases the production of anti-inflammatory factor (IL-10), and reduces the production of pro-inflammatory factors (IL-1β, IL-5, IL-6, IL-12, TNF-α) ( Lu et al, 2020 ). Additionally, a study has shown that rolipram improves endotoxin-induced cardiac dysfunction by upregulating the expression of dual specificity phosphatase 1 (DUSP1), which suppresses the secretion of TNF-α and IL-6 ( Ji et al, 2020 ). The report by Maier C et al has demonstrated that rolipram and apremilast decrease the differentiation of M2 macrophages, and reduce skin fibrosis by interfering with the release of IL-6 from macrophages ( Maier et al, 2017 ).…”
Section: Anti-inflammatory Effects Of Pde4 Inhibitorsmentioning
confidence: 99%